Hydrologic aspects of dam safety - Grigg, Neil S., editor; Colorado Water Resources Research Institute, Colorado State University, publisher (Colorado State University. Libraries, 1990)
Report of workshop held on November 16, 1989 at Colorado State University.
Organized by the Colorado Water Resources Research Institute and the Office of the State Engineer; edited by Neil S. Grigg.
Series number incorrectly printed as 162 on cover.
Keywords: Dam safety -- Congresses